PSYCHOSOCIAL FACTORS INFLUENCING PUPILS KIDNAPPING AS PERCEIVED BY PRIMARY SCHOOL TEACHERS - Ibrahim Ologele; Gbadeyanka Salim Abolaji (Indonesian Journal of Elementary Teachers Education, 2022)
Nigeria currently has more than 10 million children out of school and the school attacks and kidnappings have only made the situation worse. The study investigated psychosocial factors influencing pupil kidnapping as perceived by primary school teachers. The study adopted a descriptive research design of survey type. The study population comprised all primary school teachers in the study area. Multi-stage sampling technique was used to choose one hundred and thirty-five respondents who participated in the study. A researcher-structured questionnaire which was validated and tested for reliability was adopted for the study. A coefficient of 0.87r was obtained using the test-retest method. The instrument was administered by the researchers and three trained research assistants. Inferential statistics of chi-square used to analyse the hypotheses postulated for this study at 0.05 alpha level. The findings of this study revealed that youth unemployment influenced pupils' kidnapping because the calculated chi-square value of  61.23 was greater than the table value of 16.92 @ 0.05 alpha level, and religious fanaticism influenced pupils' kidnapping because the calculated chi-square value of 57.34 was greater than the table value of 16.92 @ 0.05 alpha level. The study concluded that the high rate of youth unemployment in our society influences pupils' kidnapping and misinterpretation of statements in holy books mislead some people to engage in kidnapping activity. The researchers recommend among others that the government at all levels should create more job opportunities for the youths graduating from school to reduce the number of young people engage in kidnapping activities due to their inability to secure employment.